Attack! : Fotografie op het scherpst van de snede - Swinnen, Johan; von Amelunxen, Hubertus; Arti et Amicitiae, Amsterdam; Andries, Pool; Berger, John; O'Brien, Edna; Dosogne, Christophe; Elias, Willem; Nakamura, Hiromi; Lemagne, Jean-Claude (Antwerpen : Houtekiet, 1999)
Abdu'Allah, Faisal ; Araki, Nobuyioshi ; Arbus, Ay ; Arke, Pia ; Attie, Shimon ; Baudrillard, Jean ; Benhelima, Charif ; Brunenberg, Jo ; Derksen, Theo ; Fontcuberta, Joan ; Hansen, Ben ; et al.
Arti & Amicitiae, Amsterdam, 5-26 juni 1999
kunstcatalogus